An ecosystem-based system of variables to enhance marine species and habitat monitoring and conservation: The Adriatic Natura 2000 case study - Manea, Elisabetta; Bergami, Caterina; Pugnetti, Alessandra; Gianni, Fabrizio; Oggioni, Alessandro; Bandelj, Vinko; Cataletto, Bruno; Pleslić, Grgur; Bongiorni, Lucia (Frontiers in Marine Science, 2022)
Implementing effective marine monitoring to detect and track ecosystem shifts, biodiversity alteration and habitat loss is one of the most crucial challenges to meet the objectives set out by the Post-2020 Biodiversity Framework and by the United Nations Sustainable Development Goals. To do so, monitoring programs should go beyond the description of individual species and habitats status, as to be able to account for the ecological complex relationships and processes that occur in marine ecosystems. Such advancement could concretely inform science-based policy decisions and conservation actions and improve our predictive capacity with respect to future changes of the marine environment. In the present study, we propose an approach to build a coherent ecosystem-based system of monitoring variables for target species and habitats by capitalizing on existing monitoring frameworks, set up by the Water and the Marine Strategy Framework directives, with the aim to contribute also to the Essential Ocean and Biodiversity Variables (EOVs and EBVs). With a holistic vision, the system is built on a classical approach to monitoring and incorporates socio-ecological aspects, considering the benefits of public engagement and the relevance of feeding an ecosystem services approach for policies’ implementation. The proposed system stems from the Ecological Observing System of the Adriatic Sea (ECOAdS), which was developed in the framework of the Interreg Italy-Croatia ECOSS project (ECological Observing System in the Adriatic Sea: oceanographic observations for biodiversity) and is applied in the context of selected Natura 2000 sites of the Adriatic Sea. We test its potential in guiding the prioritization of monitoring variables under ecosystem-based criteria, and their incorporation within the observatories’ network present in the area and the existing monitoring frameworks, to support marine conservation at both local and regional scales. This approach can be transferred to other contexts and scales to help build a common knowledge and monitoring framework, delivering concrete benefits to conservation and management strategies, saving costs by relying on available resources and on consolidated and long-lasting approaches that might converge towards global initiatives.